Impulse Response Function for Chakhutia Watershed in Ramganga Catchment, Uttranchal - Sinha, B.L.; Rastogi, R.A. (Journal of Soil and Water Conservation, 2022)
The mathematical formulation was developed for the impulse response function of Chaukhutia watershed of Ramganga river based on discrete linear input-output model to predict peak runoff rates and the temporal distribution of direct runoff on storm basis. The z-transformation and inverse z-transformation were used to develop the impulse response function. The performance and adequacy of the impulse response function was tested by comparing the computed direct runoff hydrographs with the observed runoff hydrographs. The average values of absolute relative error in estimated peak and relative mean absolute deviation were found to be 4.2771 per cent and 0.0315 respectively. These low average values indicate that the developed impulse response function generates closely comparable direct runoff hydrographs. The average value of coefficient of efficiency was found to be 0.9778, which indicates a very high degree of association between computed and observed direct runoff hydrographs.